Inspecting thermal barrier coatings by IR thermography; Thermosense XXV, Orlando, April 21, 2003 - Bison P. G. Paolo G.; Marinetti S. Sergio; Grinzato E. Ermanno; Vavilov V. P. Vladimir Platonovich; Cernuschi F. Federico; Robba D. Daniele (2003, 2003)
Title screen